Chiral auxiliary recycling in continuous flow: automated recovery and reuse of Oppolzer's sultam. Issue 8 (25th January 2018) - Sullivan, R. J.; Newman, S. G.
Abstract : The telescoping of a three-stage, chiral auxiliary-mediated transformation in flow is described, including continuous separation of the product and auxiliary, enabling automated auxiliary reuse. Abstract : The telescoping of a three-stage, chiral auxiliary-mediated transformation in flow is described, including continuous separation of the product and auxiliary. The auxiliary can either be collected for later reuse, or directly fed back to the beginning of the process for recycling in real time, enabling each molecule of auxiliary to make multiple equivalents of chiral product and thus minimizing the step- and atom-economy issues associated with auxiliary-mediated synthesis. This concept is demonstrated for the asymmetric hydrogenation of olefins using Oppolzer's sultam, shortening the total reaction time >100 fold compared to batch, and demonstrating formal sub-stoichiometric auxiliary loading with respect to the process by automating auxiliary recycling within a closed loop.